1987
DOI: 10.1901/jaba.1987.20-285
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Transition Times With Handicapped Preschool Children: A Comparison Between Peer‐mediated and Antecedent Prompt Procedures

Abstract: We examined the effects of a peer-mediated versus an antecedent prompt condition on the rate of independent movement and appropriate behavior of handicapped preschool children during three dassroom transition times. Using an alternating treatments design, results showed that each treatment condition yielded increases in target behaviors; however, the antecedent prompt condition was superior during all three transition settings. In addition, teacher prompts to these children were significantly reduced during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 8 publications
1
37
0
3
Order By: Relevance
“…Transitions, defined as a change from one activity or setting to another, can evoke disruptive behavior in young children (Sainato, Strain, Lefebvre, & Rapp, 1987). In addition, because preschoolers may spend as much as 20% to 35% of their class time in transition from one activity to another, the ability to make efficient and problem-free transitions is an important skill for school readiness (Sainato & Lyon, 1983).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Transitions, defined as a change from one activity or setting to another, can evoke disruptive behavior in young children (Sainato, Strain, Lefebvre, & Rapp, 1987). In addition, because preschoolers may spend as much as 20% to 35% of their class time in transition from one activity to another, the ability to make efficient and problem-free transitions is an important skill for school readiness (Sainato & Lyon, 1983).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Rich-lean transitions . Negative incentive shiftsTransitions between activities can account for a significant proportion of teaching time in school settings (see Sainato et al (1987) and are a ubiquitous feature of normal, everyday life. Activity transitions involve stopping the current activity and engaging in a new activity.…”
mentioning
confidence: 99%
“…Eleven studies were identified that outlined strategies for teaching transition-related behavior (Bryan and Gast 2000;Carson et al 2008;Cihak 2011;Cihak et al 2008Cihak et al , 2010Connis 1979;MacDuff et al 1993;Martin et al 1987;Massey and Wheeler 2000;Mechling and Savidge 2010;Newman et al 1995;Palmen et al 2012;Sainato et al 1987;Spriggs et al 2007). For example, Cihak (2011) compared the effects of static picture cues to video modeling on the between-task transition behavior of four students with ASD in a selfcontained classroom using an alternating treatment design.…”
Section: Antecedent-based Strategies For Teaching Transition-related mentioning
confidence: 99%